2019
DOI: 10.3390/app9071340
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Bond Behavior between GFRP Bars and Stirrups-Confined Concrete

Abstract: This paper presents the results of a series of pullout tests that were performed on Glass-fiber-reinforced polymer (GFRP) bars embedded in concrete, while providing a detailed report on the influence of various variables that impinge upon bond behavior, such as the surface characteristics and diameter of the bars, concrete strength, as well as the confined effect of stirrups. The Bertero-Popov-Eligehausen (BPE) and Cosenza-Manfredi-Realfonzo (CMR) models analyzed the bond stress (τ)–slip (s) relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Based on the typical bond-slip curves obtained from this test, the rising and falling stages of the bond-slip curves were fitted with the GDY model curve (Gao et al, 2009), quadratic model curve and mBPE model curve (Cosenza et al, 1996) to establish the bond-slip constitutive relationship between the FRP bar and SSCC. The GDY model and the quadratic model were used to compare the rising stage of the bond-slip curve of the SSCC with FRP bars, and the specific models are given in equations (2) and (3).…”
Section: Bond-slip Constitutive Modelmentioning
confidence: 99%
“…Based on the typical bond-slip curves obtained from this test, the rising and falling stages of the bond-slip curves were fitted with the GDY model curve (Gao et al, 2009), quadratic model curve and mBPE model curve (Cosenza et al, 1996) to establish the bond-slip constitutive relationship between the FRP bar and SSCC. The GDY model and the quadratic model were used to compare the rising stage of the bond-slip curve of the SSCC with FRP bars, and the specific models are given in equations (2) and (3).…”
Section: Bond-slip Constitutive Modelmentioning
confidence: 99%
“…Different types of fibers could be distinguished according to their characteristics, which condition their use. Glass fibers are widely used in the production of structural composites in the aerospace, nautical and automotive fields, associated with different matrices, for example polyamide or epoxy, still synthetic resins [13][14][15]. Glass fiber is largely used in dental field, for single, multi teeth restauration ( Figure 1).…”
Section: Glass Fibermentioning
confidence: 99%
“…The yield and transverse (stirrup) restraint of reinforcement are considered by establishing the corresponding reduction factor. Based on the study of the bond behavior of reinforced concrete under lateral pressure, Gao [20] tested the drawing specimens of glass FRP bars confined by stirrups, which showed that the confinement of stirrups to concrete changed the failure mode of concrete and the bond strength of the specimen's increases with the corresponding slip growth. The above research shows that the bond performance between reinforcement and concrete is obviously affected by the lateral compressive stress, of which the influence on the bond performance is specified in the code.…”
Section: Introductionmentioning
confidence: 99%